STRUCTURE OF THE MOLLUSK COMMUNITY IN THE INTERTIDAL ZONE OF TIRTAYASA BEACH, WAY TATAAN VILLAGE, TELUK BETUNG TIMUR DISTRICT, BANDAR LAMPUNG - Trias, Silke; Yulianto, Herman; Kartini, Nidya (AQUASAINS, 2025)
Tirtayasa Beach is a coastal tourism attraction in Bandar Lampung City, located in Way Tataan Village, East Teluk Betung District. The waters of Tirtayasa Beach have significant tourism potential due to their natural beauty. However, a decline in water quality, caused by increased human activities and domestic waste input around the beach, has affected the physical, chemical, and biological conditions of the waters. Mollusks can serve as indicators of water quality. Therefore, the structure of the mollusk community can be used to assess the condition of these waters. This study aimed to evaluate the structure of mollusk populations and analyze the influence of water quality on mollusk communities in the intertidal zone of Tirtayasa Beach, East Teluk Betung District, Lampung. The selection of study locations/stations and observation points was carried out using the purposive sampling method. The mollusks identified in the waters of Tirtayasa Beach belong to two classes: Gastropoda and Bivalvia. The Gastropoda class, with eight species, dominated across the three stations, with Cerithium kobelti being the most prevalent species. The parameter that significantly affected mollusk abundance at Station 1 was pH. At Station 2, depth, brightness, dissolved oxygen (DO), and salinity were influential. At Station 3, total suspended solids (TSS) and temperature were the key influencing factors.  Keywords: Abundance, biodiversity, evenness index, principal component analysis.